The Expression of TLR-9, CD86, and CD95 Phenotypes in Circulating B Cells of Patients with Chronic Viral Hepatitis B or C before and after Antiviral Therapy - Ping-wei Zhao; Liang Ma; Hui-fan Ji; Lei Yu; Jun-yan Feng; Juan Wang; Ming-yuan Liu; Yan-fang Jiang (Hindawi Limited, 2015)
Aims. This study aimed to assess the differential expression of specific B cell subtypes in patients with chronic viral hepatitis. Methods. The frequencies of differential expression of specific B cell subtypes in patients with chronic viral hepatitis and healthy controls were assessed by flow cytometry using monoclonal antibodies specific for CD38, CD27, CD86, CD95, TLR-9, and IgD. The effect of adefovir treatment on B cell subsets in HBV patients was determined. The values of clinical parameters in the patients were also measured. Results. The frequency of CD86+ B cells was not significantly different in chronic HBV patients but was higher in HCV patients compared with that in healthy controls. CD95 and IgD levels were lower in HBV and HCV patients than in healthy controls. A significant negative correlation occurred between the proportion of CD95+ B cells and HBV DNA viral load. The frequency of TLR-9 on the B cells in HBV and HCV patients was higher compared with that of healthy controls. After treatment with adefovir, the frequency of CD95 and IgD expressed on B cells was increased in HBV patients. Conclusions. Activated B cells and exhausted B cells homeostasis were commonly disturbed in HBV and HCV patients.